Characteristics of Astrocytoma in Indonesia - Akbar Dwi Juliardi NR (Jurnal KESANS : Kesehatan dan Sains, 2022)
Astrocytoma is a primary brain tumor originating from astrocyte cells. The study was conducted using scientific literature review methods from various sources such as google search and google scholar with relevant keywords such as “prevalensi astrositoma di indonesia”, “kejadian astrositoma di indonesia”, "prevalence of astrocytoma in Indonesia", and "epidemiology primary brain tumor in Indonesia". After reading the titles and abstracts of the articles found, there were five research articles that met the criteria. From this literature study, there were 269 cases of astrocytoma in several hospitals in Indonesia in 2007-2018. At RSUP Dr. Hasan Sadikin Bandung in 2007–2009 astrocytomas were most commonly found in patients aged 20–34 years. In 2010–2012 astrocytoma was most commonly found in patients aged 31–40 years. And in 2013-2016 astrocytomas were most commonly found in patients aged 46 to 55 years. While at RSUP Dr. Wahidin Sudirohusodo in 2016 most astrocytomas were found in patients aged 20-29 years. Astrocytoma at RSUP Dr. Hasan Sadikin Bandung in 2007-2009 was mostly located in the frontal area, in 2010-2012 astrocytoma was mostly located in the cerebral hemispheres, and in 2013-2016 astrocytoma was mostly located in the cerebellum. At RSUP Dr. Wahidin Sudirohusodo astrocytoma mostly located in frontotemporal. At RSUP Dr. Hasan Sadikin Bandung astrocytoma is more often found in men, while in RSUP. Dr. Wahidin Sudirohusodo astrocytoma is more common in female patients.